1987
DOI: 10.1530/acta.0.114s049
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid peroxidase is the organ-specific 'microsomal' autoantigen involved in thyroid autoimmunity

Abstract: Autoantibodies (aAb) in serum of patients with autoimmune thyroid diseases (AITD) are directed to an antigen associated with thyroid microsomes. Although it has been investigated over almost three decades, the nature of this autoantigen remained unknown. Taking advantage of monoclonal antibodies (mAb) produced in our laboratory, we have demonstrated that thyroid peroxidase (TPO) is the 'microsomal' antigen. Sera of patients with AITD strongly inhibited the binding of only one of 19 mAb raised against human thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Previous studies have shown that the thyroid microsomal antigen (14) and immunopurified, nonrecombinant hTPO (13) are bound by Con A. However, to our knowledge, there are no other data on the nature of the oligosaccharide (glycan) moieties in hTPO.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that the thyroid microsomal antigen (14) and immunopurified, nonrecombinant hTPO (13) are bound by Con A. However, to our knowledge, there are no other data on the nature of the oligosaccharide (glycan) moieties in hTPO.…”
Section: Discussionmentioning
confidence: 86%
“…Very little is known about the carbohydrate moieties in hTPO. hTPO (13) and the microsomal antigen (14) are bound to the lectin concanavalin A (Con A). The latter is also partially bound to lentil lectin (14).…”
mentioning
confidence: 99%
“…Выяснение причин подобной гетерогенности ауто антител у больных c различными нарушениями функции ЩЖ может уточнить патофизиологичес кие механизмы развития АИЗ ЩЖ. Одним из спосо бов решения этой проблемы является использование моноклональных антител (МкАТ) и генно инженер ных пептидов [13,23,24]. На основе сравнительного анализа специфичности МкАТ и выявляемых в сы воротке с АИЗ ЩЖ аутоантител возможно определе ние тонкой эпитопной направленности аутоантител при различных формах патологии ЩЖ.…”
Section: Introductionunclassified
“…Thyroid microsomal antibodies are circulating immunoglobulins directed against a component of the smooth endopiasmic reticulum of thyroid cells which are identical with thyroid peroxidase. Therefore the microsomal antibodies are also termed anti-TPO ab (3,4).…”
Section: Introductionmentioning
confidence: 99%